Farmers’ Varietal Preferences and Impact of Farmers Participatory Wheat Seed Production in North Western Himalayan Region - Jethi, Renu; Khulbe, Rajesh Kumar; Vasudeo, Chaudhari Ganesh; Kant, Lakshmi (Indian Journal of Extension Education, 2022)
This paper examines the impact of farmers’ participatory seed production (FPSP) of improved wheat varieties suitable for North Western Himalayan region. A wide gap exists in wheat productivity in hills and plains region of Uttarakhand, with productivity in the plains being nearly double that in the hills. Before undertaking large seed production, farmers’ preference with respect to different improved wheat varieties was recorded. The Wheat Preference Index (WPI) for VL 804, VL Gehun 829, VL Gehun 907 and VL Gehun 953 was found to be 3.64, 3.99, 4.59 and 4.61, respectively. The WPI of variety VL Gehun 953 (4.61) ranked highest majorly because of its higher productivity and superior seed quality. The cumulative growth of these varieties through FPSP was found to be 4777.2 ha in rabi 2021 from 457.2 ha in rabi 2016. The area diffusion effect of these improved wheat varieties through farmers participatory seed production was thus 10.4 times. In the year 2019-20, 145.8 quintal of seed of improved wheat variety was procured which is 10.4 times higher than the amount procured in 2015-16. Farmers earned 8.7 to 23.1 per cent higher economic gain from seed production of VL wheat varieties.
Keywords: Farmers’ preference; Wheat; Improved varieties; Seed production; Himalayan region